2022
DOI: 10.22460/project.v5i2.p288-294
|View full text |Cite
|
Sign up to set email alerts
|

Procedures of Translating Song Lyrics Into Indonesian of “Things Will Get Better” by Agnes Monica

Abstract: This study concentrated on investigating the use of the translation procedure of the translated lyrics. The objectives of the research were to find out the translation procedure used to translate song lyrics by Agnes Monica "things will get better" and the moral value in her album Agnezmo. This is a qualitative study. Data examination was paralleling the authentic language and the translated lyrics type to investigate the most used of translation procedure. The outcomes of the research displayed that there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Various studies demonstrated that lyric translators adopt the literal approach of translation. For example, according to Irawan and Mundriyah (2022), the most often employed procedure for translating ''things will get better'' by Agnes Monica's song lyrics into Indonesian was the literal translation. Literal subtitling that ignores the music is plain and uncomplicated since the translator concentrates mainly on the content and pays little attention to the form (Aleksandrowicz, 2019).…”
Section: Neglecting the Music In Translating The Lyrics (Literal Subt...mentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies demonstrated that lyric translators adopt the literal approach of translation. For example, according to Irawan and Mundriyah (2022), the most often employed procedure for translating ''things will get better'' by Agnes Monica's song lyrics into Indonesian was the literal translation. Literal subtitling that ignores the music is plain and uncomplicated since the translator concentrates mainly on the content and pays little attention to the form (Aleksandrowicz, 2019).…”
Section: Neglecting the Music In Translating The Lyrics (Literal Subt...mentioning
confidence: 99%
“…Moreover, several studies focused on. Different aspect of songs/lyrics translation, including, reception of subtitled song lyrics (Aleksandrowicz (2019), song translation options (Franzon, 2005(Franzon, , 2008(Franzon, , 2015, opera and music translation (Gorle´e, 1997), lyrics in contexts (Greenall et al, 2021), lyrics translation procedures (Irawan & Mundriyah, 2022), Principles of song translation (Low, 2003(Low, , 2005, techniques of translating lyrics (Poluwa, 2021), and others. However, it seems that the study of lyrics translation options into Arabic is not a common research area in the context of audiovisual translation studies, a gap that this study attempts to fill.…”
Section: Introductionmentioning
confidence: 99%